Drug Interactions in Type 2 Diabetes and Hypertension Patients at RSUD dr. Zainoel Abidin, Banda Aceh - Sahat Saragi; Ruhul Fitriana (Jurnal FARMASIMED (JFM), 2026)
DM(DM) is one of the diseases with a high prevalence. Indonesia ranks fifth in the world, contributing 90–95% of all diabetes cases through type 2 DM. This study aimed to identify the characteristics (age, gender, education, occupation), number of medications used, potential drug interactions, severity level of drug interactions, and the association between the number of medications and the potential for drug interactions. This was an observational study with a descriptive quantitative design and retrospective data collection. The sample consisted of 349 patients who met the inclusion criteria: patients with type 2 DM and hypertension, aged ≥18 years, receiving outpatient care at Dr. Zainoel Abidin General Hospital in 2021, and using at least one type 2 DM drug and one antihypertensive drug. The results showed that most patients were aged 56–65 years (36%), male (53.6%), had senior high school education or equivalent (46.4%), and worked as civil servants (25.8%). A total of 56.2% of patients used ≥5 medications. The most commonly used antidiabetic drug was insulin (66.44%), the most common antihypertensive was ARB (37.95%), cardiovascular prevention was dominated by statins (87.24%), and the most frequently used non-antidiabetic and non-antihypertensive drug was PPI (25.19%). A total of 92.8% of patients experienced potential drug interactions, with 1,250 total interactions. The majority were of moderate severity (85.8%) with a pharmacodynamic mechanism (78.8%). The most frequent potential interaction occurred between amlodipine and atorvastatin (3.68%). Chi-square test results showed a statistically significant relationship between the number of medications used and the potential risk of drug interactions.